In Silico Insight the Prediction of Chlorogenic Acid in Coffee through Cyclooxygenase-2 (COX2) Interaction - Bare, Yohanes; Sari, Dewi Ratih Tirto; Rachmad, Yoga Tribakti; Krisnamurti, Gabriella Candrakirana; Elizabeth, Agustina; Maulidi, Andri (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2019)
Inflammation was signs of pathological or abnormality in tissue to give an alert as a trouble signal to the system. Therapeutic using NSAIDs has some side effects. This research explored the potential role of chlorogenic acid as natural therapeutic compound to inhibit the inflammation target such as COX-2 by interaction model. The research method used in this study was the molecular docking approach, which binds ligand and protein. Protein data provided by Protein Data Bank (ID: 6cox) while, chlorogenic acid obtain from PubChem (CID: 1794427). We docked COX-2 and chlorogenic acid using Hex 8.0.0. Visualization and analysis of the molecular interactions of chlorogenic acid and COX-2 conducted by the Discovery Studio Client 4.1 software. Chlorogenic acid has a high permeability and is easily absorbed based on five Lipinski Rule. Interestingly, we found Fifteen amino acid was binding with chlorogenic acid that formed by hydrogen bond and van der Waals.The interaction between ligand-protein results in energy binding -327.59cal/mol. Chlorogenic acid has a potential role to inhibit inflammation pathway by inhibiting COX-2. We predicted chlorogenic acid has a potential as therapy anti-inflammatory to suppress COX-2 as mediator inflammation.